Coating of polytetrafluoroethylene/polyacrylate: Core‐shelled structure and tribological behaviors. Issue 29 (28th March 2019) - Wang, Na; Wang, Honggang; Ren, Junfang; Gao, Gui; Chen, Shengsheng; Yang, Yawen
ABSTRACT: In order to improve the tribological properties of polytetrafluoroethylene (PTFE), the core‐shelled PTFE/polyacrylate nanoparticles were prepared by seed emulsion polymerization and its tribological behaviors were investigated. The core–shell structure was determined by a Fourier transform infrared spectrometer and transmission electron microscopy. The results of thermoanalysis showed that polyacrylate had lost more weight than PTFE/polyacrylate composite above 300 °C, which indicated an improvement in the thermal stability. Moreover, the friction and wear results indicated that friction coefficient of PTFE/polyacrylate coating keeps at a relatively lower level, which is between that of PTFE and polyacrylate, and the wear volume is the smallest, so that an excellent performance of low friction and wear resistance was demonstrated. Besides, the tribological properties of the core‐shelled coating are maintained to be stable under high load or high speed. Therefore, the core‐shelled nanoparticles would be potential to polymer coating as high‐performance solid lubricants. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47774. Abstract :